Eksplorasi Pengalaman Coping Religius pada Penyintas Covid-19 Di Banjarmasin - Risnawati, Risnawati; Hairina, Yulia; Imadduddin, Imadduddin (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2022)
The emergence of Covid-19 pandemic all across the world including Indonesia, specifically in Banjarmasin City, is inseperable from psychological effect, that is the stress, to those who has been afflicted. Overcoming stress is different for some people, one way to do it is by religious coping. This research is a field research, in which information related to religious coping experience of Covid-19 survivors in Banjarmasin was conducted on 3 subjects using qualitative descriptive technique with phenomenological approach. The non-probability sampling technique was used based on purposive sampling from population criteria determined prior to this research. Based on the data acquired, it’s been found that religious coping aspects which can be divided into two groups, namely positive and negative religious coping, was used by all three subjects. The factors that affecting a Covid-19 survivor in doing religious coping are education, experience, and verbal thought processes (intellectuality). It is obtained that those factors are also applied to the three subjects.